Production of Meaning in Practices Involving Three-Dimensional Figurate Numbers (Global Journal of Science Frontier Research, 2025)
This study is part of a qualitative research project aimed at analyzing the production of arithmetic, geometric, and algebraic meanings through Investigative Educational Practices, based on sequences of figurate numbers, within a teacher education process involving preservice mathematics teachers. The research is epistemologically grounded in the Semantic Fields Model (SFM) and the principles of Investigative Educational Practices (IEP), which emphasize collaborative work. Based on this foundation, particularly on enunciation residues, the meanings generated by participants are analyzed using the plausible reading method, which considers both local and global interpretations. Centered on the theme of three-dimensional figurate numbers, the study explores relationships involving generalizations and recursion, fostering integration among Arithmetic, Algebra, and Geometry, especially in learning environments that value investigation and collaboration.
Keywords: mathematics education; figurate numbers; semantic fields model; investigative educational practices